Advances in synthesis, medicinal properties and biomedical applications of pyridine derivatives: A comprehensive review - Duryodhan Sahu; P.S. Rama Sreekanth; Prasanta Kumar Behera; Manoj Kumar Pradhan; Amit Patnaik; Sachin Salunkhe; Robert Cep (Elsevier, 2024)
Pyridine derivatives have emerged as promising candidates in the field of biomedical research, showcasing a wide array of applications in drug development and therapeutic interventions. The recent advances in the design and utilization of pyridine derivatives, focusing on their diverse roles in biomedical applications is the key understanding in this study. The versatility of pyridine-based compounds has been leveraged to address various challenges in the realms of pharmaceuticals and medicinal chemistry, offering innovative solutions for improved healthcare outcomes. This review encompasses the synthesis methodologies of pyridine derivatives, elucidating key synthetic strategies that enable the tailoring of these compounds for specific biomedical purposes and medicinal properties. This underscores the recent advancements in understanding the pharmacokinetics and pharmacodynamics of pyridine derivatives, emphasizing their potential impact on the future landscape of biomedical research. The synthesis and application of these compounds represent a dynamic frontier in drug development, offering innovative solutions to address unmet medical needs and propel the field toward more effective and personalized therapies. Pyridine derivatives play an important role in bio-imaging applications for the diagnosis of various diseases. Pyridine-based macromolecules have great potential for the efficient and specific delivery of drugs.